(untitled) (Journal of Information Technologies in Education (ITE), 2009)
Didactical demands for pedagogical diagnostics and its realisation specific characters under conditions of active using of ICT in instruction process of universities are analysed. The ethics questions of pedagogical diagnostics are considered. Ethic aspects, connected with using of the automated pedagogical diagnostic systems, are underlined.